Transmisi dan Kontribusi dalam Jaringan Sanad Syekh Yasin Padang - M. Khairul Mustaghfirin; Ghalby Nur Muhammad (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2021)
This article learn about The process of knowledge transmission of Muhadis Syekh Yasin Padang wich done by maintaining tradition of giving ‘ijazah sanad’ (license on chain of transmission). It enables that the teaching delivered in ontinued to the authors of book (kitab) up to prophet Muhammad (peace be upon him). The Scholars still maintains sanadan tradition. This article explains the urgency of sanad for scholarship in the transmission of religious knowledge. This study uses qualitative approach and data collected through observations. This results found that This historiography reveals the transmission of Islamic knowledge espesialy for Hadist and it saince which the Scholars of hadits “Muhaddits” attend the sanad and lisence tradition, this article explain about the methode of sanad or hadits transmision and contribution of Syekh Yasin and his idea or opinions to develop hadits sains.